DEVELOPMENT OF MICROALGA DIVERSITY MODULE AS A BIOLOGICAL LEARNING MEDIA TO IMPROVE LEARNING OUTCOMES OF X GRADE HIGH SCHOOL STUDENTS IN PROTISTA MATERIAL - Akbar, Shohifa Aulia (IJIET (International Journal of Indonesian Education and Teaching), 2021)
Microalgaeis a biological material that has an abstract nature, meaning that it cannot be directly observed by the five senses and must use certain tools to see it. The objectives of this study were: 1. Producing biology learning media in the form of modules, 2. Knowing the practicality of the module based on the activities and responses of students, 3. Knowing the effectiveness of using modules based on the achievement of indicators and 4. Knowing the feasibility of the module of microalgae diversity as a learning medium biology to improve the learning outcomes of class X high school students on protist material. This research method uses development research or R D with the development model of Borg and Gall, 1983. The results of the study based on the N-gain value showed that the experimental class got a higher score than the control class and had moderate effectiveness. Based on the validity test conducted by 3 validators, the results stated very valid so that it was suitable for use as a learning medium.